A Water‐soluble Conjugated Polymer for Thiol Detection Based on "Turn‐off" Effect. Issue 8 (29th June 2015) - Zeng, Gaoshan; Li, Jie; Liang, Hao; Yuan, Yan; Li, Xiang; Yin, Chao; Yang, Zhen; Fan, Quli; Lu, Xiaomei; Huang, Wei
Abstract We investigated a novel water‐soluble conjugated polymer (WSCP) for thiol detection based on "turn‐off" effect. This WSCP was modified with poly(ethylene glycol) (PEG) by disulfide linkages to achieve good solubility in aqueous solution (34 mg/mL) and high quantum yield (0.47). The separation of water‐soluble PEG chains from the conjugated backbone induced by the cleavage of the disulfide linkages would lead to a significant decrease of the water solubility and a dramatical fluorescence quenching of the probe. The combined intuitive images and fluorescence spectrophotometer further confirmed that decreased solubility produced an aggregation of the hydrophobic conjugated backbone. The fluorescence intensity of the probe showed a good linear relationship with glutathione (GSH) (1–200 nmol·L−1), and the detection limit was 16 nmol·L−1. This WSCP probe was confirmed to be a good sensing material with high selectivity to thiols by testing various biological molecules. And this WSCP probe exhibited good detection effect to intracellular thiols by testing Hela cells. Considering the good sensitivity and selectivity, the probe could be further used in vivo. In conclusion, this conjugated polymer probe made up for the drawbacks of the micromolecue probes and contributed to the development of new probes based on conjugated polymers.